Peran Guru dalam Menumbuhkan Karakter Peduli Lingkungan Pada Siswa di Sekolah Dasar - Dwijaya, Rezza Anugrah; Rigianti, Henry Aditia (LPPM Institut Pendidikan Nusantara Global, 2024)
The character of caring for the environment is one of the characters that must be developed in students in elementary schools because schools are part of the environment. Cleanliness of the school environment will make the learning process more comfortable for students. By accustoming students to care about the environment around them, it is hoped that they will become individuals who care about the environment. This research is a literature study using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-analyses) protocol. Research data was obtained from Google Scholar with keywords relevant to the research topic, with a time span between 2019-2023 to get the latest and related articles. From the 20 articles that were selected, then extracted and analyzed in depth, the results showed that the teacher's role is very important in fostering the character of caring for the environment in students. Teachers can guide, inspire, provide information, manage, motivate, initiate, provide facilities, demonstrate, manage classes, mediate, supervise, and assess students in developing environmentally caring characters.